2018
DOI: 10.1002/jcp.27524
|View full text |Cite
|
Sign up to set email alerts
|

Romina: A powerful strawberry with in vitro efficacy against uterine leiomyoma cells

Abstract: Uterine leiom yomas are benign tumors highly prevalent in reproductive women. In thecurrent study, initially, we aimed to screen five different strawberry cultivars (Alba, Clery, Portola, Tecla, and Romina) to identify efficient cultivars in terms of phytochemical characterization and biological properties by measuring phenolic and anthocyanin content as well as antioxidant capacity, and by measuring apoptotic rate and reactive oxygen species (ROS) production in uterine leiomyoma cells. Next, we focused on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…A recent study tested five different strawberry cultivars to identify which one presents the best phytochemical profile as an anti-UF agent. Authors found that Alba (same as in study above) and Romina cultivars presented the best results, with decreased collagen 1A1, fibronectin, versican, and activin A mRNA expression in UF cells [169]. Strawberry and its potent anthocyanins might offer therapeutic or preventive spectrum in UF treatment.…”
Section: Anthocyaninsmentioning
confidence: 69%
See 2 more Smart Citations
“…A recent study tested five different strawberry cultivars to identify which one presents the best phytochemical profile as an anti-UF agent. Authors found that Alba (same as in study above) and Romina cultivars presented the best results, with decreased collagen 1A1, fibronectin, versican, and activin A mRNA expression in UF cells [169]. Strawberry and its potent anthocyanins might offer therapeutic or preventive spectrum in UF treatment.…”
Section: Anthocyaninsmentioning
confidence: 69%
“…Plants that are rich in those pigments include blueberries, raspberries or strawberries [167]. According to two studies, strawberries anthocyanin are of special interest in UFs [168][169][170]. Strawberries have anti-inflammatory, anti-oxidative, anti-proliferative, and genomic protective effects [169,171].…”
Section: Anthocyaninsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following that, the same group of researchers investigated the anti-UF activity of five different cultivars of strawberry. It was identified that Romina followed by the Alba cultivar produced the most promising anti-UF activity, which suggests its potential in using strawberry extract as an alternative treatment for UF ( Giampieri et al, 2019 ).…”
Section: Botanical Drugs With Anti-uterine Fibroid Activitymentioning
confidence: 99%
“…We also highlighted that the anticancer activities of strawberry were ascribed to its capability to regulate some genes involved in different cancer‐related molecular pathways: for example, in uterine benign leiomyomas, strawberry extract (250 μg/ml for 48 hr) and its anthocyanin fraction (50 μg/ml for 48 hr) promoted apoptosis, increased the levels of ROS, affected glycolysis, and reduced the expression of genes involved in fibrosis, a feature of this type of tumor, such as collagen 1A1, fibronectin, versican, and activin A (Giampieri et al., 2019), whereas in murine breast N202/1A (with high levels of HER2/neu oncogene) and N202/1E (with low levels of HER2/neu oncogene) cancer cells, strawberry extract (175–200 μg/ml for 48 hr) and its anthocyanin fraction (175–200 μg/ml for 48 hr) were able to play antiproliferative effects, through the induction of oxidative stress and apoptosis, by regulating the expression of several proteins involved in the antioxidant system, in apoptosis and in mitochondrial biogenesis and functionality, including AMPK, PGC‐1α, SIRT3, nuclear factor erythroid 2‐related factor 2 (Nrf2), caspase 3, and cytochrome b–c1 complex subunit 1 (Mazzoni et al., 2019). Similarly, in murine breast A17 cancer cell line, strawberry (0.5, 1, 2.5, and 5 mg/ml for 48 hr) stopped cell cycle in phase G1 and decreased cellular mobility by regulating the expression of several genes involved in invasion, cellular migration, and adhesion processes, such as the colony stimulating factor 1 (Csf1), the nuclear receptor subfamily 4, group A, member 3 (Nr4a3), the melanoma cell adhesion molecule (Mcam), SET nuclear proto‐oncogene (SET), matrix metalloproteinases 10 and 3 (Mmp10 and Mmp3), and integrin beta 3; interestingly, the anticancer activities of strawberry were further confirmed in an in vivo study, where the growth of A17 cells orthotopically transplanted into FVB syngeneic mice was inhibited by strawberry consumption (15% of total diet calories) (Amatori et al., 2017).…”
mentioning
confidence: 99%